Simbol, Metafora, dan Makna Kehidupan dalam Antologi Hujan Bulan Juni Karya Sapardi Djoko Damono: Kajian Hermeneutika Paul Ricoeur - Fitri Dwi Jayanti; Dede Endang Mascita; Diki Mutaqin (Jurnal Bahasa dan Sastra, 2026)
Poetry is one of the literary literacy materials that can develop students' interpretive, reflective, and appreciative abilities. However, the use of symbols and metaphors often makes poetry difficult to understand because its meanings are not conveyed directly. This study aims to describe and analyze the symbols and metaphors found in the poems of Sapardi Djoko Damono's Hujan Bulan Juni anthology, interpret the meanings of life represented through these symbols and metaphors, and explain their relevance as literary literacy materials for senior high school students. This study employed Paul Ricoeur's hermeneutic approach using a qualitative descriptive method. The data consisted of words, phrases, lines, and stanzas containing symbols and metaphors in five poems: “Lanskap”, “Tulisan di Batu Nisan”, “Yang Fana Adalah Waktu”, “Aku Ingin”, and “Berjalan ke Barat Waktu Pagi Hari”. Data were analyzed through the stages of distanciation, appropriation, and refiguration. The findings reveal the presence of natural, temporal, color, situational, and abstract symbols, as well as the use of anthropomorphic and concrete-to-abstract metaphors. These symbols and metaphors construct meanings of life related to reflections on life's journey, acceptance of loss, awareness of the limitations of time, sincerity in giving and letting go, and the importance of making peace with oneself. The findings also indicate that the poems in Hujan Bulan Juni are relevant as literary literacy materials for senior high school students because they can foster students' interpretive, reflective, and literary appreciation skills. Based on the complexity of their symbols and metaphors, Aku Ingin and Lanskap are more suitable for Phase E, while Berjalan ke Barat Waktu Pagi Hari, Yang Fana Adalah Waktu, and Tulisan di Batu Nisan are more suitable for Phase F.